Infiltration Analysis of Paving Block Cover on the Basis of Embankment Soil Variations - Andayono, Totoh; Maulina, Melan (Universitas Negeri Padang, 2023)
The large amount of infrastructure used causes less green land for rainwater absorption, so that rain that falls on the ground is not absorbed optimally. The resulting surface runoff is more than the amount of water absorbed. To overcome this, the method is to reduce the use of impermeable land cover (concrete pavement) and replace it with appropriate surface land cover. One of the efforts made is the use of pervious paving to reduce surface runoff and increase infiltration. This test aims to determine how much infiltration rate and capacity occurs when using paving block cover with variations in embankment soil. This research uses quantitative methods with an experimental approach using an artificial rain simulator. The soil used in this research is soil sourced from Lubuk Alung, Sarik River and Mount Sarik. The paving blocks used are in the form of hexagons which are usually used as ground surface pavement. Infiltration testing carried out several analyzes namely infiltration rate, infiltration capacity and cumulative infiltration. The results of this research show that good infiltration is the Sarik River landfill with the use of paving block cover, the infiltration rate value is 0.619-0.112 cm/minute, the infiltration capacity is 6.18 cm/hour, the cumulative infiltration is 8.97 and runoff occurs in the second minute. 09 and the chart intersects at the 30th minute. The results of infiltration testing using an artificial rain simulator showed that the use of paving block cover can increase infiltration thereby reducing the occurrence of run off.